2014
DOI: 10.1007/s00253-014-5557-2
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms living on macroalgae: diversity, interactions, and biotechnological applications

Abstract: Marine microorganisms play key roles in every marine ecological process, hence the growing interest in studying their populations and functions. Microbial communities on algae remain underexplored, however, despite their huge biodiversity and the fact that they differ markedly from those living freely in seawater. The study of this microbiota and of its relationships with algal hosts should provide crucial information for ecological investigations on algae and aquatic ecosystems. Furthermore, because these mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
113
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 162 publications
(167 reference statements)
0
113
0
2
Order By: Relevance
“…Within microbial communities, negative interactions such as competition or predation can be detected along with mutually beneficial or synergistic interactions such as cross-feeding, co-metabolism or cell-to-cell communication (21)(22)(23). Photo-and chemolithoautotrophic microbes interact with heterotrophic microbes in many different environments (24,25). For example, macro-and microalgae live with specific heterotrophic microbial subcommunities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within microbial communities, negative interactions such as competition or predation can be detected along with mutually beneficial or synergistic interactions such as cross-feeding, co-metabolism or cell-to-cell communication (21)(22)(23). Photo-and chemolithoautotrophic microbes interact with heterotrophic microbes in many different environments (24,25). For example, macro-and microalgae live with specific heterotrophic microbial subcommunities.…”
mentioning
confidence: 99%
“…For example, macro-and microalgae live with specific heterotrophic microbial subcommunities. The exchange of nutrients, enzymes, and bioactive compounds in these communities results in increased community productivity (24,25). AOB have been shown to interact positively with NOB and heterotrophic bacteria (26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…To our knowledge, however, nobody has yet performed functional screening of metagenomic libraries from algal microbial communities. As algal microbial biofilms are in constant interaction with algal biomass, they represent an interesting source of enzymes and other active compounds (18). Sequence-based studies have already revealed the importance and functions of microbial communities living on the surfaces of algae, showing tight interdependence between algae and their biofilms (19)(20)(21).…”
mentioning
confidence: 99%
“…Among the bacteria known to interact with algae, Flavobacteriia, and notably several species of Zobellia, have been found in association with macroalgae (31)(32)(33) and have been isolated from phytoplankton (34) and from seawater (35). The interactions between Zobellia strains and marine algae range from symbiosis, with some strains inducing the normal differentiation of green macroalgae (36), to algicidal behavior toward dinoflagellate blooms (34).…”
mentioning
confidence: 99%